Nafkah Pasca Talak bagi Istri Nusyuz: Telaah Yuridis atas Putusan Mahkamah Syar'iyah Banda Aceh Nomor 215/Pdt.G/2020/Ms.Bna - Nisa Ulkhuluq; Aulil Amri; Nurul Fithria (An-Nisa: Journal of Islamic Family Law, 2025)
This study aims to analyze the legal considerations of judges in determining post-divorce alimony to wives who are declared nusyuz in the practice of religious justice. In classical Islamic law, nusyuz wives are generally not entitled to alimony, but the reality in Indonesian religious courts shows that there is flexibility in its interpretation and application. This study uses a normative juridical approach with a qualitative descriptive method, based on a study of the Decision of the Banda Aceh Syar'iyah Court Number 215/Pdt.G/2020/MS. Bna. The data was analyzed through a review of laws and regulations, a Compilation of Islamic Law, and fiqh books as the main source of law. The results of the study show that even though the wife is proven to be nusyuz, the judge still determines the maintenance of iddah and mut'ah by considering social factors, such as the economic condition of the wife and the existence of young children. This consideration shows that there is a contextual approach by judges that prioritizes the principles of justice and protection for vulnerable parties. This study concludes that the practice of providing alimony to nusyuz wives can be legally justified if it is based on the principle of benefit. Therefore, it is necessary to understand the law that is adaptive to social dynamics and strengthen regulations that are in line with the sharia maqashid in realizing substantive justice in Indonesian religious courts.